Tacticity effects in side-chain photoluminescent polymers. Issue 97 (19th November 2018) - Chiang, Cheng-Hung; Huang, Shih-Hung; Nien, Po-Chun; Chiang, Yeo-Wan; Tsai, Jing-Cherng
Abstract : A significant red shift (or blue shift) can be observed by increasing the degree of isotacticity (or syndiotacticity). Abstract : Stereoregular side-chain photoluminescent (PL) polymers were synthesized via the stereospecific polymerization of 9, 9-dibutyl-2-(4-vinylphenyl)-9 H -fluorene. The resulting isotactic, syndiotactic and atactic poly(9, 9-dibutyl-2-(4-vinylphenyl)-9 H -fluorene) polymers were used as stereoregular polymer samples for examining the configurational tacticity effect on their PL properties. Our results revealed a unique tacticity-dependent effect as observed by an obvious red-shifting of the PL emission by increasing the degree of isotacticity of these stereoregular polymers; despite the ultraviolet spectra of these polymers exhibited similar absorption patterns. This study provides a new structural design for the syntheses of PL polymers.